Praktek Pengenalan Lapangan SD Negeri 03 Probur Utara - Welhelmina Rahayu Laumalay,; Yermias S. Wabang,; Madayani Potmo,; Pilmon Karmaley, (Student Scientific Creativity Journal, 2024)
Field Introduction Practice (PPL) is an activity carried out by students to get to know and understand directly field conditions related to the field of study being studied. This activity aims to provide practical experience to students so that they can apply the theory they have learned on campus to real situations in the field. Field introduction practices are often carried out in various disciplines, such as education. Field introduction practice aims to get to know real conditions in the field. Providing a direct understanding of the conditions or situations that exist in the world of work or fields that are relevant to the study being carried out. Application of theory. Connecting theory that has been studied in class with practice in the field, Providing opportunities for students to hone practical skills needed in the world of work or certain professional fields, Career Preparation Equipping students with relevant experience to prepare them to face challenges in the professional world.